ChemInform Abstract: Vulgarisin A, a New Diterpenoid with a Rare 5/6/4/5 Ring Skeleton from the Chinese Medicinal Plant Prunella vulgaris. Issue 42 (14th October 2014) - Lou, Huayong; Zheng, Shan; Li, Tianlei; Zhang, Jianxin; Fei, Yue; Hao, Xiaojiang; Liang, Guangyi; Pan, Weidong
Abstract shows weak cytotoxicity against human lung carcinoma A549 cells